Nanographene Sheet Immobilized Transition Metal Complexes for C-C Coupling Reactions - Anuma, Saroja; Ramachandra Bhat, Badekai (International Journal of Engineering and Technology, 2018)
Transition metal Schiff base complexes covalently immobilized on the surface of amino functionalized graphene sheet to catalyze C-C coupling reaction is reported. Graphene sheet which synthesized using mechanical exfoliation and then by differential oxidative reduction phenomenon of graphite. The schiff base ligand is prepared using aldehyde and amino groups containing compounds which further treated with metal salts to form metal complexes. The as-synthesized metal complexes was then incorporated into amino functionalized nanosheets which are characterized using different spectrochemical techniques. The catalytic investigation of the as-prepared catalyst were done by the cross coupling of aryl halides and aryl boronic acids to form biaryls as product in C-C cross coupling reaction. The yield of the products were high and selective which were analyzed using Gas chromatography technique. The advantage of this catalyst is high stability, recyclability easy recovery of catalyst, environmentally benign and mild reaction condition. Â Â